Analisis Epistemological Obstacle Siswa Dalam Menyelesaikan Soal Cerita Matematika Berdasarkan Gaya Kognitif - Rizki Dwi Siswanto (Universitas Muhammadiyah Prof. Dr. HAMKA Press, 2020)
This study aims to determine the causes and describe the epistemological obstacle in students completing the math problem's operation based on cognitive style. The method used in this study is descriptive qualitative. The epistemological obstacle analyzed in this study are misconceptions, procedural errors, and technical errors, while the cognitive styles categorized in this study are field dependent and field independent. In this study, we processed data analysis using qualitative descriptive statistics and through three activity lines, namely data reduction, data presentation, and data verification or drawing conclusions, and used to get descriptive answers based on test data and interviews. The Group Embedded Figures Test (GEFT) test is used to determine students' cognitive style categories who will be categorized as independent fields and dependent fields. While the test of the mathematical story matter of the operating material calculates the fractions analyzed by the epistemological obstacle. We interviewed to gather information from the study subjects on an epistemological obstacle that occurred in students in solving mathematical story problems based on cognitive style. The research results revealed that students with independent fields and dependent fields still often make misconceptions, procedural errors, and technical errors in solving mathematical problem material in fractional calculation operations. Keywords: Learning Obstacle, Epistemological Obstacle, Cognitive Style, Field Independent, Field Dependent